NuSTAR Observations of a Varying-flux Quasar in the Epoch of Reionization - Lea Marcotulli; Thomas Connor; Eduardo Bañados; Peter G. Boorman; Giulia Migliori; Brian W. Grefenstette; Emmanuel Momjian; Aneta Siemiginowska; Daniel Stern; Silvia Belladitta; C. C. Cheung; Andrew Fabian; et al. (The Astrophysical Journal Letters)
With enough X-ray flux to be detected in a 160 s scan by SRG/eROSITA, the z = 6.19 quasar CFHQS J142952+544717 is, by far, the most luminous X-ray source known at z  > 6. We present deep (245 ks) NuSTAR observations of this source; with ∼180 net counts in the combined observations, CFHQS J142952+544717 is the most distant object ever observed by the observatory. Fortuitously, this source was independently observed by Chandra ∼110 days earlier, enabling the identification of two nearby (30″ and 45″ away), fainter X-ray sources. We jointly fit both Chandra and NuSTAR observations—self-consistently including interloper sources—and find that, to greater than 90% confidence, the observed 3–7 keV flux varied by a factor of ∼2.6 during that period, corresponding to approximately two weeks in the quasar rest frame. This brightening is one of the most extreme instances of statistically significant X-ray variability seen in the Epoch of Reionization. We discuss possible scenarios that could produce such rapid change, including X-ray emission from jets too faint at radio frequencies to be observed.